Pengaruh Penambahan Abu Tandan Sawit Dan Variasi Fly Ash Terhadap Nilai CBR Dan Permeabilitas Tanah - Saputra, Arkam; Lebang, Fauzy; Mallawangeng, Tamrin (Program Studi Teknik Sipil Universitas Bosowa, 2023)
Soft clay soil has a relatively low subgrade bearing capacity and relatively large subgrade compression and lasts for a relatively long time so that it becomes a major problem in the development of transportation infrastructure. The aim of the research is to determine the effect of a mixture of palm bunch ash and variations of fly ash on the CBR value of clay soil and to determine the effect of a mixture of palm bunch ash and variations of fly ash on the permeability of clay soil. One of the efforts to improve soft clay soil is by adding palm bunch ash as a stabilizing agent on the soil. This study uses a variation of ash of palm bunches as much as 7.5% and fly ash of 0%, 15%, 30%, 45% of dry soil weight. The result of CBR penetration of Original Soil is 6.9% and for the addition of 7.5% Palm Oil Bunches + 0% Fly Ash decreased by 4.8%, however the CBR value increases with the addition of Fly Ash percentage, 15% Fly Ash + 7.5% Palm Oil Bunches the CBR value is 5.3% , Fly Ash 30% + Oil Palm Bunches 7.5% CBR value of 5.8% and with the addition of Fly Ash 45% + Oil Palm Bunches 7.5% an increase in CBR value of 6.1%, while the results of the Permeability Coefficient of Original Soil are 0.000888 and for Original Soil with the added material of 7.5% Palm Bunches and 0% Fly Ash of 0.0013 with a difference of 0.000412, while the addition of fly ash variations for the variation of 7.5% Palm Bunches + 15% Fly Ash the permeability value of 0.0007 decreased permeability